2017
DOI: 10.3390/rs9101060
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of WorldView-2 Red-Edge Band-Based Vegetation Indices for Estimation of Mangrove Leaf Area Index with Machine Learning Algorithms

Abstract: Abstract:To accurately estimate leaf area index (LAI) in mangrove areas, the selection of appropriate models and predictor variables is critical. However, there is a major challenge in quantifying and mapping LAI using multi-spectral sensors due to the saturation effects of traditional vegetation indices (VIs) for mangrove forests. WorldView-2 (WV2) imagery has proven to be effective to estimate LAI of grasslands and forests, but the sensitivity of its vegetation indices (VIs) has been uncertain for mangrove f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 81 publications
7
62
0
4
Order By: Relevance
“…All the regression models were run on the calibration dataset and the associated parameters were optimized using five-fold cross-validation with 10 repeated experiments. Five-fold cross validation was preferred over 10-fold cross validation because of the limited sample size [28,46]. Finally, variable importance was determined to analyze the contribution of each predictor variable to prediction accuracy of the best models.…”
Section: Four Linear and Non-linear Multiple Regression Methods Inclmentioning
confidence: 99%
See 1 more Smart Citation
“…All the regression models were run on the calibration dataset and the associated parameters were optimized using five-fold cross-validation with 10 repeated experiments. Five-fold cross validation was preferred over 10-fold cross validation because of the limited sample size [28,46]. Finally, variable importance was determined to analyze the contribution of each predictor variable to prediction accuracy of the best models.…”
Section: Four Linear and Non-linear Multiple Regression Methods Inclmentioning
confidence: 99%
“…Thus, machine learning methods based on artificial neural networks (ANNs) and random forest regression (RFR) have been utilized to capture both linear and non-linear relationships that exist between remote sensing and vegetative parameters [24][25][26]. Yuan et al [27] and Zhu et al [28] demonstrated that RFR was superior to ANNs in leaf area index (LAI) prediction due to its suitability for a relatively small number of training samples and insensitivity to noisy data [29]. Recently, Pôças et al [30] demonstrated the power of machine learning methods to support irrigation scheduling in vineyards using data from a handheld spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…2019, 11, 345 7 of 24 B5 (705 nm) bands, provided high correlations during estimation of the leaf area index and the chlorophyll content. Pu et al [59] and Zhu et al [60] introduced the operational use of this index for the Worldview-2 satellite imagery. To the best of our knowledge, this research is a novel evaluation of the NDVIre on operational Sentinel-2A imagery.…”
Section: Pre-processing Of the Satellite Images And Extraction Of Spementioning
confidence: 99%
“…These features were selected based on their previous performances in mangrove species discriminations, mangrove biomass inversions or other vegetation studies, as highlighted in literature [14,24,25,[45][46][47][48]. EVI (enhanced vegetation index), for example, enhances vegetation signals by adding blue bands to correct soil background and aerosol scattering effects, which is suitable for areas with high leaf area index values [17]. The spectral features consisted of conventional NIR indices, red edge indices and shortwave infrared indices.…”
Section: Spectral and Textural Featuresmentioning
confidence: 99%